PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS TEORI BRUNER BERMUATAN KARAKTER UNTUK SEKOLAH DASAR - Supriyono; Rintis Rizkia Pangestika (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2021)
The aims of this research are to: produce mathematics teaching materials based on Bruner's Theory containing appropriate characters for elementary schools. The research method used is the ADDIE Research and Development model, which consists of five stages, namely analysis, planning, development, implementation, and evaluation. The population in this study was the fifth grade students of SD N Ngupasan, totaling 30 students. Data collection techniques used are interviews and questionnaires. The analytical technique used is descriptive and quantitative statistics. The results of this study indicate that product validation data by learning device experts is obtained in the